An empirical examination of the use of bargaining power and its impacts on supply chain financial performance. Issue 4 (October 2019) - Cho, Woohyun; Ke, Jian-yu Fisher; Han, Chaodong
Abstract: This study empirically examines how benefits of resource dependence may be bargained away by supply chain finance (SCF) costs incurred to upstream suppliers and downstream buyers through cash conversion cycles. We found that a focal firm may get compensated for its resource contribution with an extra share of the financial gains by using the superior bargaining position over its supply chain partners. Nevertheless, the focal firm may proactively restrain its use of bargaining power when the need for cooperative relationship with its supply chain partners prevails. Managerial and research implications for the introduction of power theory and relation theory to the SCF studies are discussed. Highlights: We examine how benefits of resource dependence may be bargained away by supply chain finance costs through cash cycles. A focal firm may obtain an extra share of the financial gains by using its superior bargaining position over its partners. A focal firm may proactively restrain its use of bargaining power when there are needs for cooperative relationship.